MabÄá¸¥iá¹¡ al-ÄªmÄn âalÄ Naáºrah Ahl as-Sunnah wa al-JamÄâah: DirÄsah âan Makhá¹Å«á¹ah Naáºm al-waá¹£iyyah li asy-Syaikh Muhammad Saâid Bonjol al-MÄ«nangkÄbÄwÄ« - Hadi, Sofyan (Center for Research and Development of Religious Literature and Heritage, 2013)
-